Kompetensi Komunikasi Antar Budaya Peserta Pelatihan dari Indonesia di Australia - Luthfia, Amia (Humaniora, 2011)
This research studied about intercultural communication competency Indonesians when they study in Australia. Having competency in communicating with different cultures is important in order to avoid intercultural conflict, also to establish effective and proper communication. Although the training participants have different cultural background with Australians, obviously they are competent enough to conduct intercultural communication especially in social formal context. However, in social informal context, they are not competent enough. The training participants are competent in social formal context because they are helped by education setting that accommodative and tolerance towards their weaknesses compared to social informal context.